A clinical guide to autistic spectrum disorders - Evans, Patricia, 1956- (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2011)
"Sad to say, most medical school and residency programs fail to prepare physicians very well to recognize the less obvious forms of autism spectrum disorder or to appropriately manage children with autism. Clinical neuroscience training, at whatever level, tends to emphasize global failure of cognitive development or the subsequent loss of one or more cognitive functions due to structural lesions or diffuse degenerative processes. Neither of these models suit children with autism spectrum disorders very well. Inexperience in the management of autism has become particularly problematic because of the increased frequency of its diagnosis in recent years and the increased recognition of milder autism phenotypes"--Provided by publisher.